RealityCheck: Blending Virtual Environments with Situated Physical Reality - Hartmann, Jeremy; Holz, Christian; Ofek, Eyal; Wilson, Andrew D. (Proceedings of ACM CHI 2019, 2019)
Today’s virtual reality (VR) systems offer chaperone rendering techniques that prevent the user from colliding with physical objects. Without a detailed geometric model of the physical world, these techniques offer limited possibility for more advanced compositing between the real world and the virtual. We explore this using a realtime 3D reconstruction of the real world that can be combined with a virtual environment. RealityCheck allows users to freely move, manipulate, observe, and communicate with people and objects situated in their physical space without losing the sense of immersion or presence inside their virtual world. We demonstrate RealityCheck with seven existing VR titles, and describe compositing approaches that address the potential conflicts when rendering the real world and a virtual environment together. A study with frequent VR users demonstrates the affordances provided by our system and how it can be used to enhance current VR experiences.